The roles of public relations in an environmental awareness campaign: a case study of SWM Environment Sdn Bhd - Abdul Rahim, Shahrul Amir; Markom, Mohd Nasir; Syed Alsagoff, Syed Agil (Penerbit UTM Press, 2019)
Conducting an environmental awareness campaign by using the qualitative research method exemplifies how public relations (PR) can boost the impact towards audience’s behavior. Generally, PR practitioners have their own strategies in delivering messages, but there are certain roles that influence the audience’s behavior, attitude and mentality. This warrants further investigation on the failure factors of current environmental awareness campaigns which revolve around communication theories in obtaining more enlightening and reasonable facts. This study examines the professionalism of PR practitioners and personnel using in-depth interviews and content analysis by reviewing related documentation to understand underlying dynamic practices. The findings will construct the real challenges that implicate the PR practitioners’ role and the audience’s reaction towards environmental awareness campaigns in Malaysia.